Hepatitis C Treatment of Patients With Bipolar Disorder: A Case Series - Rifai, Muhamad Aly (Physicians Postgraduate Press, Inc., 2006)
Background: Hepatitis C virus (HCV) chronic infection affects 10% to 15% of patients with bipolar disorder. Patients with HCV infection and comorbid psychiatric illness pose a tremendous clinical and therapeutic challenge. The cases presented in this report illustrate several critical issues facing clinicians who manage patients with comorbid HCV infection and bipolar disorder. Method: Five cases are described in which patients with DSM-IV bipolar disorder were treated with interferon-α–based therapies and ribavirin to induce viral clearance of HCV. In all cases, the patients were treated using an integrated model of care, and the treatment decision was a consensus between the treating hepatologists and psychiatrists. Results: In the first case, the patient had no significant neuropsychiatric adverse effects and had viral clearance. In 2 other cases, viral clearance of HCV was achieved through the delicate management of affective symptoms induced by interferon-α and ribavirin. Interferon-α and ribavirin treatment was halted due to mania and suicidal ideation in the 2 remaining cases. Conclusion: These cases suggest that patients with hepatitis C and bipolar disorder should be evaluated for HCV antiviral treatments, as these patients can receive and tolerate these treatments if assessed meticulously, observed carefully, and followed extensively during interferon-α and ribavirin treatment. This case series will hopefully spark a dialogue about when HCV antiviral treatment should be withheld or delayed in these difficult cases.